Policy settings supporting Australia’s Blue Economy - Marcus Haward (2019)
The blue economy is expected to provide significant opportunities in the first half of twenty-first century around the globe. Maritime Australia extends from tropical to Antarctic waters and includes numerous marine biogeographic provinces and environments. These areas support an array of marine resources and uses and contain diverse and globally important environments with a range of both intrinsic and use values. This paper explores current regulatory and policy base for Australia offshore resource and environmental management. The paper outlines and highlights the strong influence of “offshore federalism”, the constitutional, legal and political frameworks that shape the management of offshore activities and the protection of the marine environment. The paper provides a snapshot overview of Australia’s maritime domain and the opportunities and challenges associated with emerging blue economy activities. The paper concludes with an assessment of regulatory and policy coherence, capacity and alignment of current policy settings underpinning blue economy operations. Development an effective policy framework for the emergent blue economy Australia will enhance and complement a range of current activities in the ‘marine and coastal ‘space’. It will also have considerable links to current initiatives in maritime Australia. A focus on vertical and horizontal governance, and of institutional arrangements to address problems related to maritime issues also addresses the question of policy capacity and coherence. Key agencies need to be able to maintain and extend its own capacity, and be able to display leadership in this area, but they also need to be able to work effectively with the range of other actors engaged in work that will contribute such responses.